Variation of Resistance Responses on Indicator Plants Against Odontoglossum ringspot virus (ORSV) Infection - Mahfut (International Journal of Advanced Science and Technology, 2020)
Odontoglossum ringspot virus (ORSV) is a orchid virus which infection most widely reported and has spread widely in the world, including in Indonesia. Viral infections can degrade the quality of the orchid plant so it is economically detrimental. The early stages of disease control can be done through the introduction of infection symptoms that appear. This research was conducted to study the response of some plant of indicator plant against a single infection of ORSV trough mechanical inoculation. Futhermore, virus detection on plants tissue were done trough the DAS-ELISA and RT-PCR. The results showed that Chenopodium amaranticolor is the only indicator plant that shows a susceptible response with a characteristic symptom, namely necrotic local lesion. Whereas Nicotiana tabaccum and Nicotiana benthamiana showed susceptible responses to symptoms of severe ORSV infection, namely mosaic, chlorotic, and leaf malformations. The variation of resistance from several indicator plant against infection ORSV showed severe symptoms with the incubation periode was seen earlier. This indicate an infection of ORSV is a dangerous disease and require serious control.